PENDAMPINGAN MASYARAKAT KURANG MAMPU MELALUI KELOMPOK USAHA BERSAMA (KUBE) DI DAERAH PERKOTAAN - Sahir, Syafrida Hafni; Rosmawati, Rosmawati; Koryati, Try (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
The high rate of poverty and economic inequality in urban areas requires an inclusive and sustainable economic empowerment strategy. This service aims to strengthen the economic independence of underprivileged communities in urban areas through the Joint Business Group (KUBE) approach. By increasing income, diversifying businesses, and expanding the collaboration network, KUBE members will develop further. This service method uses Participatory Action Research (PAR) involving intensive and continuous assistance to KUBE members, including business skills training, strengthening business models, and collaboration with microfinance institutions and local governments in Binjai Timur, Kota Binjai, Sumatera Utara. The results of the service show a significant increase in KUBE members' income, with an average increase of 30% in one year. Business diversification also occurred with the success of KUBE members adding 3 new products to their business portfolio, increasing competitiveness and local market access. Strengthening cooperation networks is also a positive result of this service, with the establishment of collaborations that provide additional access to resources and economic opportunities. The conclusion of this service confirms that assistance through KUBE is effective in increasing the economic independence of underprivileged communities in urban areas. This program not only provides training, but also builds independent capabilities, expands markets, and strengthens the local business ecosystem, thereby providing a sustainable positive impact in improving community welfare.